Unsafe abortion among secondary school girls in a local authority in South-South Nigeria - Abah, Matthias G.; Bassey, Emem E.; Edu, Emmanuel B.; Ovie, Okupa D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Voluntary abortion for social reasons is illegal in Nigeria; however, the practice remains mostly clandestine and unsafe with varying consequences and determinants yet to be studied in all settings. Methods: A descriptive cross-sectional study design was used to assess the prevalence, practice and determinants of termination of pregnancy amongst 119 female Secondary School students in South-South Nigeria. Results: The prevalence of abortion was 57.1%. Most of the students were above 18years (58.8%), Christian (95.8%) and of rural residence (66.4%). While 58.8% had experienced an unwanted pregnancy, 61.4% had used some form of contraceptive with condom being the commonest (39.5%). Most (89.1%) have heard of abortions while 67.6% and 16.2% have had abortions once and twice respectively with the top reasons for abortion being that they were still in school (33.8%), too young (25.9%) and to avoid shame or stigma associated with the pregnancy (11.7%). Dilation and curettage was the predominant method employed (40.2%) mainly by medical doctors (34.1% and pharmacists (35.6%) while 51 (75%) had post-abortal complaints such as pain (41.2%) and bleeding (21.6%). There was a significant association between having an abortion and place of residence (rural more than urban), (p=0.04), being pregnant more than once (p<0.001), mothers` level of education (p=0.03), fathers` level of education (p=0.02) and mothers occupation (p=0.04). Conclusions: The prevalence of abortion is high and complicated by high morbidity rate despite a higher contraceptive prevalence rate whose major determinants were the socio-demographic characteristics of the parents. There is a need for early sex education from parents as this can influence abortion perception and practice in later years.